(untitled) (Bangladesh Journal of Medical Education, 2019)
Presence of MEU in medical colleges has been made as a measure of activities in National Quality Assurance guidelines for the improvement of medical education as well as faculty development. So, it is imperative to assess its activities in medical colleges for the expected outcomes which might facilitate administrators and policy makers for logical intervention where needed. Considering this matter, a descriptive type of cross sectional study was carried out to assess the status of activities of MEU in medical colleges of Bangladesh. Data was collected from 26 medical colleges of Bangladesh selected by purposive sampling method and 324 related available teachers by convenient sampling methods using a self-administered semistructured questionnaire. Total 26 MEUs coordinators or acting in charge as Key Informants were interviewed by using an interview schedule. A checklist was used for observation of existing MEU while visiting medical colleges for data collection. Principal/Vice Principal of medical colleges had responded to mailed letter as well as telephonic call and replied to have formal MEU at 20 (91%) out of 22 government and at 81 (98.2%) out of 83 non-government medical colleges. Around 87 % faculty members usually attend the MEU activities which is conducted by MEU coordinators in 75 % cases. CME program, pre and para clinical issue related activities occur in 70 % cases. The experiences gained from MEU activities are utilized 88 % in undergraduate class room, 59 % in conducting CME activities and around 50 % in other MEU activities. Staff related, Structural, faculty related, and administrative barriers have been identified by respondents and adequate fund and experienced staffs, motivation of faculty members and continued administrative monitoring can overcome those barriers (is it opinion? Of whom?). Key Informants opined MEU to take leading role in medical education development. Faculty members related to MEU should be adequately trained to impart interactive and effective education in both class room and bedside teaching. Policy level support, specific flow of fund, motivation and will of medical administrators and faculty members and proper monitoring by CME were found to be effective in establishing and functioning MEU in medical colleges. Bangladesh Journal of Medical Education Vol.10(2) 2019: 12-18